2003
DOI: 10.1108/09513570310492290
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of corporate social responsibility: the nature of managerial capture

Abstract: Furnishes a narrative reflecting an in‐depth examination of managerial conceptions of corporate social responsibility (CSR) in the Irish context. The narrative locates itself within the debate surrounding the extent to which corporate management may capture social accountants’ efforts to promote a broad society‐centred conception of CSR. Three key findings emerge from the narrative. First, there is evidence of a tendency for managers to interpret CSR in a constricted fashion consistent with corporate goals of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
287
3
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(311 citation statements)
references
References 57 publications
8
287
3
13
Order By: Relevance
“…First, interviews asking for the understanding of a concept can be conducted with relevant stakeholders, but it has been found that these stakeholders oftentimes struggle to provide thoughtful responses ad hoc (Johnston and Beatson, 2005;O'Dwyer, 2003;Dahlsrud, 2008). Second, written definitions of a concept can be gathered and then analysed.…”
Section: Methodsmentioning
confidence: 99%
“…First, interviews asking for the understanding of a concept can be conducted with relevant stakeholders, but it has been found that these stakeholders oftentimes struggle to provide thoughtful responses ad hoc (Johnston and Beatson, 2005;O'Dwyer, 2003;Dahlsrud, 2008). Second, written definitions of a concept can be gathered and then analysed.…”
Section: Methodsmentioning
confidence: 99%
“…A rather consolidated stream of the social and environmental accounting literature argues that the absence of established auditing standards reduces accountability to external audiences and stakeholders groups (see, for example, Power 1997; Gray and Bebbington 2000;Dando and Swift 2003;O'Dwyer 2003;Adams 2004;Cooper and Owen 2007;Smith et al 2011). …”
Section: Previous Research On Sustainability Assurance and Research Qmentioning
confidence: 99%
“…It can be assumed that the inherent opacity around sustainability assurance fails to demonstrate convincingly organizational accountability because these practices are subject to 'capture' by powerful managerial and professional interests (Ball et al, 2000;O'Dwyer andOwen, 2005, 2007). On the demand side, senior company management or professional associations tend to take control of or 'capture' sustainability policy and practices by appropriating the language and processes of traditional financial auditing in order to meet their own commercial and professional objectives (cf.…”
Section: Previous Research On Sustainability Assurance and Research Qmentioning
confidence: 99%
“…Despite the evidence that businesses, especially large corporations, have steadily increased the volume of corporate responsibility and sustainability information in their corporate reports (Gray, et al, 1995;KPMG, 2005;2008;, concerns endure that for many, corporate responsibility reporting remains a mask behind which 'business as usual' continues, unreconstructed (Christian Aid, 2004;Gray, 2006). Some organisations have attempted to capture the agenda and redefine the terminology to make it appear that sustainability is easily managed and delivered (Ball, et al, 2000;Gray, 2006;Muir, et al, 2002;O'Dwyer, 2003), and others have challenged its usefulness as a concept (Lélé, 1991;Robinson, 2004) .…”
Section: Introductionmentioning
confidence: 99%